2006
DOI: 10.1139/l06-044
|View full text |Cite
|
Sign up to set email alerts
|

Study of recycled polyethylene materials as asphalt modifiers

Abstract: There has been interest in modifying asphalt with polyethylene materials, which are a major plastic waste substance, especially low-density polyethylene (LDPE). In this study, combinations of three low molecular weight polyethylene (PE) wax materials and three recycled LDPE materials were used as asphalt modifiers. The modified asphalts were studied using the Superpave TM MP1 and MP1a specifications, 1% direct tension test (DTT) failure strain criteria, phase separation, and microscopy. When the molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 28 publications
(29 reference statements)
3
28
0
1
Order By: Relevance
“…They investigated the rheology of binders incorporating large amounts (up to 40%) of recycled plastic and found these blends to be thermodynamically incompatible. Ho et al (2006) investigated the use of recycled low density polyethylene with polyethylene wax and found that polymers with lower molecular weights tended to disperse more evenly within the asphalt binder but again focussed on rheological behaviour of the modified binder. Hinislioglu & Agar (2004) investigated the use of recycled high density polyethylene (HDPE) as a binder modifier for asphalt samples, using the Marshall Stability test as an indicator.…”
Section: Polymer Modification Of Bitumensmentioning
confidence: 99%
“…They investigated the rheology of binders incorporating large amounts (up to 40%) of recycled plastic and found these blends to be thermodynamically incompatible. Ho et al (2006) investigated the use of recycled low density polyethylene with polyethylene wax and found that polymers with lower molecular weights tended to disperse more evenly within the asphalt binder but again focussed on rheological behaviour of the modified binder. Hinislioglu & Agar (2004) investigated the use of recycled high density polyethylene (HDPE) as a binder modifier for asphalt samples, using the Marshall Stability test as an indicator.…”
Section: Polymer Modification Of Bitumensmentioning
confidence: 99%
“…A large number of polymers have been studied for bitumen modification, including polyethylenes (Jew et al, 1986;Bahl et al, 1993;Fawcett et al, 1999a), polyolefins (Morrison et al, 1994;Fawcett and McNally, 2000a;Fawcett et al, 1999b;Yousefi, 2003), most Introduction to polymer modified bitumen (PmB) extensively styrene homopolymers and copolymers (Airey, 2004;Bahl et al, 1993;Blanco et al, 1995;van Beem and Brasser, 1973;Vonk, 1988, 1992;Lu and Isacsson, 2001;Varma et al, 2002;Vonk and Bull, 1989;Heimerikx, 1993;van Gooswilligen and Vonk, 1986;McNally, 2001a, 2003;Wang et al, 2007;Gonzêlez-Águirre et al, 2009), ionomers (Engel at al., 1991), ethylene vinyl acetate and acrylic copolymers (Denning and Carswell, 1981;Fawcett and McNally, 2001b), rubbers (Fawcett and McNally, 2000b), polymer blends (Fawcett et al, 2002; and many other polymeric materials (Boutevin et al, 1989;Fawcett et al, 2000). More recently, there has been intense interest in the use of recycled or scrap plastic, including tyre rubber crumb to modify bitumen (Singh et al, 2003;Ho et al, 2006;Fang et al, 2008;Fuentes-Audén et al, 2008;Cao et al, 2008;Navarro et al, 2010;Naskar et al, 2010).…”
Section: Polymer Modified Bitumenmentioning
confidence: 99%
“…Hence considerable difference in effects of asphalt modifying and segregation property exist in both PMB and PMA. Canadians Susanna Ho, Ronaca Church, Kristel Klassen, Barkley Law and so on once proved in their study that lower molecule PE and wider molecule amount PE materials are better asphalt modifying agents [3] . So PMB has better storage stability and small segregation is due to: (1) its molecule amount distribution is wider, solubility parameter δ is not a relatively fixed values but a wider range.…”
Section: Mechanism Of Segregation Resistance Of Waste Used Plastic Momentioning
confidence: 99%